Credit constraints and consumer spending - Kimberly Beaton (Bank of Canada, 2009)
This paper examines the relationship between aggregate consumer spending and credit availability in the United States. The author finds that consumer spending falls (rises) in response to a reduction (increase) in credit availability. Moreover, she provides a formal assessment of the possibility that credit availability is particularly important for consumer spending when it undergoes large changes. In this respect, she estimates a consumption function in which only large expansions and contractions in credit affect spending. She concludes that large changes in credit availability are particularly important for consumers' spending decisions. As should be expected, these periods tend to be associated with periods of high economic uncertainty. These results show that credit availability should be taken into account when modeling and forecasting consumer spending.
Keywords: E21; E27; E44; E51; E58; 330; Credit and credit aggregates; Domestic demand and components; Recent economic and financial developments; Privater Haushalt; Kreditwürdigkeit; Verschuldungsrestriktion; Haushaltseinkommen; Gesamtwirtschaftlicher Konsum; USA